Efektivitas Kebijakan Dana Desa Bagi Pembangunan Ekonomi Dan Infrastruktur Pedesaan Di Kabupaten Oku Timur - Priyaning Rahayu, Ika; Yani, Nurma; Widia Putri, Refi; Panorama, Maya (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2022)
Village funds used for village development aim to improve community welfare, improve quality of life and reduce poverty and those used for village community empowerment aim to increase the capacity of citizens in entrepreneurial development, increase income, and expand individual economic areas of community groups. One way to strengthen the rural economy is to improve the rural infrastructure which aims to enlarge the existing potential and make the countryside the backbone of the regional and national economy. Rural development is multi-aspected. Therefore, it is necessary to conduct a more focused analysis and linkages with sectors and aspects outside the countryside (physical and non-physical, economic and non-economic, social and cultural, and non-spatial).